An advanced tri‐culture model to evaluate the dynamic interplay among osteoblasts, osteoclasts, and endothelial cells. Issue 1 (3rd May 2017) - Pagani, Stefania; Torricelli, Paola; Veronesi, Francesca; Salamanna, Francesca; Cepollaro, Simona; Fini, Milena
Abstract : The dynamic metabolism and the numerous roles of bone tissue necessitate a suitable in vitro model to represent them. In order to investigate the interaction among the several cell types composing bone microenvironment, we studied a tri‐culture model including human osteoblasts (OBs), osteoclasts (OCs), and endothelial cells (HUVEC). While OBs are essential for bone deposition and OCs for bone resorption, the vasculature is necessary to provide growth factors, nutrients, and oxygen in the mature tissue. The results of this study showed a strong mutual influence between OBs, OCs, and HUVEC in term of proliferation, viability, and activity (release of ALP, Coll I, OPG, RANKL, VEGF, CTSK, TGFβ, and IL‐6). The behavior of the single cultures demonstrated to be different compared to the bi‐ or tri‐cultures and depending on the cell types involved: the coexistence of OBs and OCs stimulated the synthetic activity of both cell types, while the presence of HUVEC induced a stimulating role for OBs but mainly an inhibitory effect for OC. In addition, evidence of the effects of OBs and OCs on HUVEC is highlighted by their morphology: regular and able to "sketch" little vessels in presence of OBs, more disorganized and heterogeneous in presence of OCs. Taken together, these observations well characterize an advanced cellular model to be used as starting point for mimicking bone microenvironment in vivo, thus reducing the use of animals in the preclinical phase and offering a more reliable tool to test new and innovative biomaterials. Abstract : In vitro model of direct co‐colture showing the mutual influence among osteoblast for bone deposition, osteoclast for bone resorption and endothelial cells for angiogenesis, as starting point in mimicking in vivo microenvironment.